Systematic literature review of project failures: Current trends and scope for future research. (January 2019) - Gupta, Sandeep Kumar; Gunasekaran, Angappa; Antony, Jiju; Gupta, Shivam; Bag, Surajit; Roubaud, David
Highlights: This paper presents the first comprehensive and systematic literature review of failed projects. Most of these failed project studies were conducted in the information technology sector due to its project-based nature. Less effort has been made to analyse the similarities and differences in project monitoring and performance assessment. Identified the need for more research on project failure predictions under dynamic scenarios. Proposed an input-process-output model for project monitoring and evaluation. Abstract: Although projects are considered indispensable elements across many industries, practitioners and researchers have realised that projects' high failure rates are costing many firms several million dollars a year. This paper presents the first comprehensive and systematic literature review of failed projects. In our research, we noticed an increasing trend in publications for case study-based research which limits the generalising of the findings due to the customised nature of these projects. Most of these failed project studies were conducted in the information technology (IT) sector due to its project-based organisational structure. We found that less effort has been made to analyse the similarities and differences in project monitoring and performance assessment approaches under diverse scenarios (e.g., process improvement, R&D, etc.). We also identified the need for more research on project failure predictions under dynamic scenarios, and we therefore recommended the input-process-output model for project monitoring and evaluation.